Potentials and implementation of digitisation at company level - Michael Hüther (Wirtschaftsdienst)
Abstract Digitisation at the corporate level has long been a practical component of strategic planning and implementation. Specific effects on productivity growth or employment can be shown on the basis of producer-customer relationships. With regard to productivity growth, it is to be expected that increases will be delayed and that there is still untapped potential in many areas. Positive employment effects can be expected especially in the business-to-business market, while the business-to-consumer market, which is dominated by the large tech companies, has comparatively low employment figures. The bottom line is that there will increasingly be a change in the competence requirements. The challenge is not to lose out on less innovation-affine companies and fewer IT-affine employees.